Pengembangan video animasi pembelajaran matematika berbasis nilai-nilai kewirausahaan di sekolah dasar - Rilia Ayuni; Romadon Romadon; Adevia Indah Kusuma (University of Muhammadiyah Malang, 2022)
Increasing entrepreneurial values in practice needs to be supported by good learning media. This project is intended to create animated video media for learning mathematics based on entrepreneurial principles for second graders of elementary school. The research employed Research and Development (R&D) develoipmental model by using the ADDIE method. Two media experts, two material experts, and one linguist expert served as the research subjects. User responses from the results of the implementation consisted of 2nd grade homeroom teachers and 38 students in 2nd grade of SD Negeri 8 Air Gegas in South Bangka. The data collection method employed questionnaires and observation as the instrument of the research. An average rating of 90.2% from media professionals was reached after considering the opinions of material specialists, linguists, and media experts. Based on the assessment of media experts, material experts, and linguists, an average percentage of media experts' assessment of 90.2% with very appropriate criteria, 82.5% of material experts with very feasible criteria, and 88.4% of linguists with very feasible criteria was obtained. Based on the responses of students and teachers, it was obtained an average percentage of students' assessment of 95% with very practical criteria and 89.4% of teachers with very practical criteria. While the results of the post test obtained an average percentage of 86.2% with very effective criteria. This research drew the conclusion that the media produced using the Animaker software is very feasible and practical to be implemented in learning and is effective in efforts to increase entrepreneurial values in students. The research suggested that the media can be used by teachers in the learning process by paying attention to other supporting facilities, while in further research to be able to measure the implementation of this media over a longer period of time using learning outcomes instruments.